(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
This research attempts to present a new reading of Anaxagoras philosophy on the basis of showing that it was the first in the history of Greek philosophy to pose major philosophical problems that preoccupied later philosophers, such as: the Eternal world, and the division of existence into concrete and reasonable. The research also seeks to provide a critical reading of the positions of Aristotle and Plato of the philosophy of Anaxagoras, and their negative impact on the understanding of historians of Greek philosophy of the philosophy of Anaxagoras.